2019
DOI: 10.1002/term.2912
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the WNK1 kinase to corneal wound healing using the tissue‐engineered human cornea as an in vitro model

Abstract: Damage to the corneal epithelium triggers important changes in the extracellular matrix (ECM) to which basal human corneal epithelial cells (hCECs) attach. These changes are perceived by integrin receptors that activate different intracellular signalling pathways, ultimately leading to re‐epithelialization of the injured epithelium. In this study, we investigated the impact of pharmacological inhibition of specific signal transduction mediators on corneal wound healing using both monolayers of hCECs and the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 58 publications
3
23
0
Order By: Relevance
“…details have emerged only recently. WNK463 inhibits corneal wound healing and reduces filopodium formation in engineered corneas and cultured corneal epithelial cells where WNK1 is the predominant WNK isoform expressed (Desjardins et al, 2019). A pathway including WNK1, SPAK and NKCC1 mediates vascular tone and the pressor response to α 1 adrenergic agonists in WNK1 +/− mice (Bergaya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…details have emerged only recently. WNK463 inhibits corneal wound healing and reduces filopodium formation in engineered corneas and cultured corneal epithelial cells where WNK1 is the predominant WNK isoform expressed (Desjardins et al, 2019). A pathway including WNK1, SPAK and NKCC1 mediates vascular tone and the pressor response to α 1 adrenergic agonists in WNK1 +/− mice (Bergaya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…WNK1 participates in fundamental biologic processes including angiogenesis, and mitosis (Xie et al, 2009(Xie et al, , 2013Tu et al, 2011;Gallolu Kankanamalage et al, 2016). WNK1 kinase is also involved in cell migration and adhesion where it controls cytoskeletal structure and migration-associated local cell volume fluctuations as demonstrated in endothelial cells, T cells, corneal epithelial cells and certain cancers, notably glioblastoma cells (Haas et al, 2011;Dbouk et al, 2014;Zhu et al, 2014;Kochl et al, 2016;Desjardins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent attempt to further characterize the mechanistic details of the signal transduction pathways activated during corneal wound healing, we have shown that phosphorylation-mediated activation of the WNK1 kinase was one particularly important event occurring during hTEC wound healing [ 336 ] ( Figure 7 ). WNK1 is the founding member of a family that comprises four evolutionarily conserved serine–threonine kinases (WNK1, WNK2, WNK3, and WNK4) that share 85% homology over their kinase domains [ 337 ].…”
Section: The Future Of the Htec: Potential Applications And Usesmentioning
confidence: 99%
“…( C ) Cell lysates from the central and external areas of wounded hTECs were analyzed by immunoblotting to confirm the phosphokinase array results for the mediator WNK1. Actin was used as the loading control (Figure adapted from Reference [ 336 ] with the permission of Journal of Tissue Engineering and Regenerative Medicine).…”
Section: Figurementioning
confidence: 99%
“…Vesicating agents are reported to cause clinical and histopathological changes related to inflammation and blistering in the eye that are results of alkylation, oxidative stress, lipid peroxidation, and induction of inflammatory responses (Goswami et al 2016). Corneal models have been useful in studying molecular mechanisms of vesication to aid in the development of therapies against oxidative stress and vesicant-induced ocular injuries (Desjardins et al 2019;Kaluzhny et al 2020). Also, ocular surface diseases were addressed using an in vitro 3D stromal model of keratoconus disease (Karamichos et al 2012) and a model of endothelial cell maturation to study endothelial layer differentiation and injury (Hutcheon et al 2019).…”
Section: Dry Eye Disease and Other Ocular Surface Injury And Disease Applicationsmentioning
confidence: 99%